2022
DOI: 10.52380/ijpes.2022.9.2.705
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study on Online Teaching during the Covid-19 Pandemic Perceived by Primary School Teachers

Abstract: Research shows that teachers are one of the most influential factors in student learning in online classrooms during the COVID -19 pandemic and discusses teachers' efforts to get the most out of their online classrooms with their students. However, how the teachers experience online teaching is understudied. To address this concern, this case study aimed at revealing the experiences of primary school teachers in online teaching during the COVID-19 pandemic with a particular focus on the difficulty in teaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…In addition to these feelings, some teachers in the current research referred to their low digital literacy that affected their confidence in conducting online teaching. Like in other studies, teachers felt insecure and overwhelmed by the sudden need to perform online teaching using advanced technologies, and were facing problems integrating technology with pedagogy and subject teaching (Pattnaik et al, 2023;Sari & Saralar-Aras, 2022). Teachers claim that low online teaching proficiency, may have caused them high levels of burnout during the COVID-19 pandemic (Gutentag & Asterhan, 2022).…”
Section: Discussionmentioning
confidence: 96%
“…In addition to these feelings, some teachers in the current research referred to their low digital literacy that affected their confidence in conducting online teaching. Like in other studies, teachers felt insecure and overwhelmed by the sudden need to perform online teaching using advanced technologies, and were facing problems integrating technology with pedagogy and subject teaching (Pattnaik et al, 2023;Sari & Saralar-Aras, 2022). Teachers claim that low online teaching proficiency, may have caused them high levels of burnout during the COVID-19 pandemic (Gutentag & Asterhan, 2022).…”
Section: Discussionmentioning
confidence: 96%
“…This led to impacts on students' learning interactions, collaborations and engagement outcomes. Through homeschooling, it was difficult for parents who had limited teaching skills to create a conducive learning environment to ease students' learning and adaptability (Masanyiwa et al, 2023). Learners with learning difficulties and disabilities also faced inadequate development of practical or psychomotor skills and received improper handling of their learning environment and allocation of learning resources.…”
Section: Challenges Faced In Sped Amidst Covid 19mentioning
confidence: 99%
“…Even before Covid 19, children with disabilities have experienced and suffered a lot from education access inequities and learning outcomes (Smith et al, 2022). Although the pandemic affected the education system worldwide, teachers, parents and students, however, the impacts vary among students due to their natural setting, backgrounds and conditions (Masanyiwa, Mwamakula & Mhagama, 2023). Students with special needs suffered a lot in coping with homeschooling and difficult situations amid COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of these studies indicate that online learning has a negative impact on students' academic achievement, including in mathematics. Other studies (Putra et al, 2020;Rasmitadila et al, 2020;Sarı & Aras, 2022) found that students struggle to understand mathematical concepts virtually, and the lack of direct interaction with teachers and classmates affects their ability to apply mathematical concepts.…”
Section: Introductionmentioning
confidence: 99%